Fundamentals for the Anthropocene - Pearce, Jack (De Gruyter, 2017)
This book seeks to bridge the gap between leading edge scholarship about the nature of the physical, tangible Universe and the nature of the life process on Earth on the one hand, and on the other hand challenges facing human society as to the current revolution in energy sources, national and international levels of political and economic organization, and humanity`s impacts upon the global ecosystem which have given rise to the depiction of a new era in earthlife termed the anthropocene.The author`s public career included responsibilities for economic policy formulation and implementation at the United States Department of Justice, the United States Agency for International Development, and a White House Office of Consumer Affairs. This provided an elevated overview of many current economic and political issues.These responsibilities stimulated a multi-decade exploration of leading academics` insights into the relational structuring of the Universe, non-equilibrium thermodynamics, complexity in the universe, and the structure of the life process. This book applies such fundamental insights to the question whether humanity will succeed or fail in its ambitious but uncertain quest.